Trade Union Growth: A Marketing Model - Gilson, Clive; Spencer, Ian (Relations industrielles / Industrial Relations, 1987)
By fusing trade union theory and marketing strategy, this paper provides an interdisciplinary perspective to the study of trade union structure.